2017
DOI: 10.20435/1984-042x-2017-v.18-n.1(09)
|View full text |Cite
|
Sign up to set email alerts
|

Expansão agrícola: elaboração de indicadores de sustentabilidade nas cadeias produtivas de Mato Grosso do Sul

Abstract: Resumo: A Lei 12.651 surgiu da necessidade dos agropecuaristas em aumentar a sua produção versus a conservação da vegetação nativa. Assim, é possível aumentar a produção agropecuária consonante a Lei vigente, podendo citar o decreto que trata do Programa Mato Grosso do Sul Mais Sustentável. É importante que todos os proprietários de terra venham seguir as recomendações que estão previstas na lei para que o Estado não venha enfrentar a escassez de água que ocorreu em São Paulo em 2014. Palavras-chave: Lei 12.65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
0
4
0
4
Order By: Relevance
“…The soybean (Glycine max L. Merryl) is currently one of the main commodities of Brazilian agribusiness, which has become a source of income and prosperity for many producing regions of the country (BORLACHENCO; GONÇALVES, 2017;ARTUZO et al, 2018). In the 2017/2018-crop season, soybean presented a seeded area of 35,022.8 hectares with an average productivity of 3.156 kg ha -1 , and these values have values increasing in recent years (CONAB, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The soybean (Glycine max L. Merryl) is currently one of the main commodities of Brazilian agribusiness, which has become a source of income and prosperity for many producing regions of the country (BORLACHENCO; GONÇALVES, 2017;ARTUZO et al, 2018). In the 2017/2018-crop season, soybean presented a seeded area of 35,022.8 hectares with an average productivity of 3.156 kg ha -1 , and these values have values increasing in recent years (CONAB, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Faine (1982) concluded that, compared to temperate regions, disease presence and dispersion are more favored in tropical and subtropical regions due to persistent bacteria in flooded environments, where they can survive for up to 180 days, depending on temperature (28 °C to 30 °C) and pH (7.2 to 7.4) conditions. In Mato Grosso do Sul, the tropical climate prevails in most of the territory, characterized by rainy summers and dry winters, with average temperatures varying between 26°C in the Paraguay lowlands and 23°C in the Plateau, and approximately 1,500 mm rainfall annually (Borlachenco & Gonçalves, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An agricultural expansion of 87% was observed in the Cerrado from 2000 to 2014, and 76% of this increase was caused by soybean (Carneiro Filho & Costa, 2016). Sustainable practices need to be established in the economic, social, and environmental spheres using new technologies and management that allow equal or greater production without increasing areas already cultivated (Borlachenco & Gonçalves, 2017).…”
Section: Introductionmentioning
confidence: 99%